APPLICATION OF INVENTORY MANAGEMENT IN MSME DETAC CAFÉ - Hery Haryanto; Tiffany Lim (ConCEPt - Conference on Community Engagement Project, 2022)
This study aims to implement inventory management at MSME Detac Café in 2021 and 2022 using the EOQ, ROP, and SS methods. The results of data analysis are used to determine the optimal number of orders with the aim of dealing with uncertainty in demand as it is known that there is a possibility of fluctuating demand, so as to satisfy customer demand and minimize storage costs. Inventories that are calculated in this study are coffee beans, milk, cream, cheese, and tea. Based on the results of interviews with the owner, it shows that the MSME Detac Café inventory system is still not effective so that there is no stock storage cost efficiency. The results of this study indicate that the calculation used is able to reduce inventory costs in the form of storage and delivery costs for Detac Café. By implementing this inventory management, MSMEs can achieve a more efficient total inventory cost.